Analysis and Countermeasures for EMU Traction Motor Stator Insulation Faults - Chunlong NA; Hui PENG; Yulong WANG (Chengshi guidao jiaotong yanjiu, 2024)
[Objective] To ensure the reliability of the stator insulation in EMU (electric multiple unit) traction motors during stator manufacturing or maintenance, it is necessary to conduct tests such as ground insulation withstand voltage, interphase withstand voltage, and coil-to-coil insulation withstand voltage to screen for defects of stator-to-ground insulation, interphase insulation, and coil-to-coil insulation. Therefore, an analysis of stator insulation faults in traction motors is required, and corresponding countermeasures are proposed. [Method] The fault characteristics and causes of ground insulation breakdown, interphase short circuit, and non-coinciding waveform attenuation in coil-to-coil insulation are introduced. Corresponding improvement measures and stator repair methods for these faults are analyzed. [Result & Conclusion] After repair, the stator of traction motor successfully passes the screening tests for ground insulation withstand voltage, interphase withstand voltage, and coil-to-coil insulation withstand voltage, and the test results demonstrate that the analyzed fault causes can accurately diagnose stator insulation faults, and the formulated improvement measures effectively resolve stator insulation issues.